Forecasting Financial System Stability Using Vector Error Correction Model Approach - Setiawan, Setiawan; Utomo, Moch. Trianto; Astuti, Alfira Mulya; Akbar, M. Sjahid; Ahmad, Imam Safawi (CAUCHY, 2020)
Indonesia is one of the developing countries whose economic system is still very dependent on other developed countries. This reliance often becomes one of the causes of the occurrence of economic turmoil sectors that interfere with financial system stability in Indonesia. Therefore, to forecast financial system stability indicators, primarily macroeconomic variables, become essential to do to provide an accurate index value. Then, Forecasting signs of stability of the financial system in Indonesia using Vector Error Correction models (VECM) approach with financial system stability indicators used are Banking Stability Inde